Development of macro and micro-nutrient rich integrated Jeevamrutha bio-fertilizer systems using rural and commercial precursors - Udaratta Bhattacharjee; Ramagopal V.S. Uppaluri (Energy Nexus)
Cow dung-based bio-fertilizers often requires additional organic amendments to demonstrate the nutritional necessities for field applications. Thereby, the present study validated the need for an integrated farming technique with the readily available rural and commercial precursors (such as vermicompost, neem cake, tea waste and water hyacinth) into the cow-excreta-based Jeevamrutha organic bio-fertilizer. Hence, physio-chemical, nutritional content and microbial characteristics were targeted. The ratios of Jeevamrutha and the above-mentioned precursors were varied as 1:4 for vermicompost, 1:3 for neem cake, 1:2 for tea waste and 1:3–1:4 for water hyacinth at an ambient temperature between 12 and 38ºC during winter and summer seasons respectively. The wide range of temperature was considered to accomodate the average temperatures of summer and winter seasons of Guwahati, India. Nutritional factors such as total Kjeldahl nitrogen (TKN), ammonium nitrogen (AN) and phosphate (P) was maximum for tea waste-integrated Jeevamrutha bio-fertilizer. These respectively varied as 1.94–3.22 %, 726.8–1076.4 mg/L and 0.57–0.65 % during the winter and summer seasons. Similar nutrient trend was followed by neem cake-integrated Jeevamrutha bio-fertilizer (TKN:1.78–2.24 %; AN:623.4–873.56 mg/L and P:0.64–0.71 %) during winter and summer seasons. Phytotoxicity assay shows that desired concentration of the optimal compositional set was 50 % (v/v) and 20 % (v/v) for the seasons. Cost analysis for the bio-fertilizer systems revealed a minimal expenditure associated for tea waste (Rs. 10.56/kg) followed by water hyacinth-integrated Jeevamrutha bio-fertilizer (Rs. 12.68/kg) in comparison with the conventionally used jaggery-based Jeevamrutha bio-fertilizer (Rs. 17.3/kg). Here, jaggery refers to the product obtained as a product in rural India.